Twisting macromolecular ladder for fast-charging and long-life lithium batteries
By synthesizing twisted conjugated ladder-shaped macromolecules as cathode materials for lithium-ion batteries, the problems of low conductivity and poor cycle stability were solved, and the performance of lithium-ion batteries with fast charging and high power density was achieved.
Patent Information
- Application Number
- CN202380029018.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-25
- Filing Date
- 2023-03-24
- Publication Date
- 2025-01-07
AI Technical Summary
Existing lithium-ion batteries experience a decrease in power density and cycle stability during charge-discharge cycles. In particular, the low conductivity of inorganic electrode materials leads to long charging times and significant capacity loss. Furthermore, organic electrode materials are prone to dissolution during redox reactions, which affects battery performance.
A twisted, fully conjugated ladder-shaped macromolecule design was employed to synthesize a helical perylene diimide macromolecule via the Suzuki reaction and Mallory photocyclization sequence, forming an electrode material with high electrical conductivity and high ionic conductivity for use as a lithium-ion battery cathode.
This lithium-ion battery achieves fast charging and long lifespan, with charging time reduced to approximately 35 seconds, output power density up to 22,000 W/kg, excellent cycle stability, and minimal capacity decay after 10,000 cycles.
Smart Images

Figure CN119278518A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This PCT application claims priority to U.S. Provisional Patent Application No. 63 / 323,753, filed on March 25, 2022, the entire contents of which are incorporated herein by reference.
[0003] Statement of Government Interest
[0004] This invention was made with government support from the National Science Foundation (NSF) under DMR-2002634 and from the Office of Naval Research (ONR) under N00014-20-1-2477. The government has certain rights in this invention. Background Art
[0005] The disclosed subject matter relates to the field of lithium-ion batteries, and more particularly, to molecular arrays of twisted macromolecular ladders for organic battery electrode materials for fast-charging and long-life lithium-ion batteries.
[0006] Lithium-ion battery (LIB) is an energy storage system that has accelerated the development of today's information society. Some LIBs can have relatively high performance, but during the charge-discharge cycle, the power density and cycle stability decrease. This can be particularly serious for many applications such as electric vehicles, because their charging time is relatively long and the capacity loss after hundreds of cycles is considerable.
[0007] Compared to certain inorganic electrode materials, OBEM can provide high power density and energy density simultaneously, for example due to the molecular tunability that can provide high ion diffusion coefficient and high specific capacity. OBEM also has relatively low production cost, low environmental impact, and can be sustainable in view of the natural abundance of its components. However, OBEM may also have reduced specific capacity and relatively poor cycle stability because the organic molecules may be immersed in the electrolyte solution during redox reactions. In view of such deficiencies, organic polymers can be used, however, they may have low charge capacity due to the non-redox reactive linkers and solubilizing side chains. In addition, the relatively low intrinsic conductivity of OBEM may reduce its ability to achieve high rate performance and area mass loading, resulting in the incorporation of large amounts of conductive additives in order to achieve acceptable results.
[0008] Therefore, there is a need to provide macromolecules and materials that can be used in lithium batteries to provide sustainable, fast-charging, and long-life lithium batteries. Summary of the invention
[0009] The disclosed subject matter relates to organic battery electrode materials (OBEMs) and provides methods and techniques for preparing macromolecules, such as twisted and fully conjugated macromolecules, and battery cathodes containing the macromolecules. Such macromolecules can form fast-charging and long-life cathodes for incorporation into lithium batteries.
[0010] The disclosed subject matter solves these and other needs by providing a molecular array design of a distorted fully conjugated ladder macromolecule. In certain embodiments, the macromolecule can be distorted at one or more aromatic sites. In certain embodiments, the macromolecule can be distorted at six aromatic sites. The macromolecular structure defined on the atoms of the disclosed subject matter, which is fully conjugated and long, can be synthesized by a synthetic scheme. In certain embodiments, the macromolecule is configured to have at least a ladder-type conjugated structure and a plurality of hPDI[n] oligomers, wherein n is an integer from 1 to 6, such as hPDI[6].
[0011] The disclosed subject matter also provides methods comprising a repeated Suzuki reaction-Mallory photocyclization sequence that can provide quantitative photocyclization to, for example, generate short spiroperylene diimide [2] (hPDI[2]-C 11 ) Preparation of helical perylene diimide [6] (hPDI[6]-C 11 ). In certain embodiments, a method for synthesizing a molecular array of a twisted and conjugated macromolecular ladder is provided. In certain embodiments, the method comprises preparing a precursor having a plurality of hPDI[n], wherein n is an integer from 1 to 6, and polymerizing the precursor by repeated Suzuki-Mallory polymerization process to form a twisted and conjugated macromolecular ladder having a ladder-type conjugated structure and comprising hPDI[n].
[0012] In certain embodiments, the PDI subunits are fused via ethylene subunits.
[0013] In certain embodiments, the polymerization process includes modeling the conjugation length and distortion of the macromolecular ladder. In addition, the method can include increasing the length of the π-conjugation and the number of distorted aromatic sites for adjustment. In certain embodiments, hPDI[n] is composed of hPDI[n]-C 11 preparation.
[0014] In certain embodiments, hPDI[n] has a conjugated and twisted band structure.
[0015] The disclosed subject matter also provides an electrode for use in a lithium ion battery comprising a molecule of a twisted fully conjugated ladder macromolecule. In certain embodiments, the molecule is formed as a cathode.
[0016] The disclosed subject matter provides lithium ion batteries including electrodes using molecules of twisted fully conjugated ladder macromolecules.
[0017] The synthetic scheme of the disclosed subject matter can provide the synthesis of longer bands by avoiding incomplete photocyclization (e.g., synthesis of hPDI[n], up to n=4). In certain embodiments, the alkyl chains can be quantitatively removed, for example, by vacuum pyrolysis. Such a process for removing alkyl chains can increase the gravimetric capacity, for example, by reducing the non-electroactive mass, and can also render the material insoluble. In certain embodiments, the structure of the resulting macromolecule can be determined, for example, by 13 C solid-state nuclear magnetic resonance (NMR), infrared spectroscopy, matrix assisted laser desorption / ionization (MALDI) mass spectrometry, or a combination thereof. In certain embodiments, the macromolecule can be a twisted helical perylene diimide [6] (hPDI [6]) macromolecule. In such embodiments, six (6) redox-active PDI subunits can be fused together, for example, by ethylene subunits. Such macromolecules can exhibit high rate performance and cycling stability.
[0018] In certain aspects, by adjusting the length of the hPDI[n] oligomer, the electrical conductivity and ionic conductivity of the material can be adjusted simultaneously. The length of the ladder of the oligomer macromolecule can adjust the conjugation length, and the distortion can achieve lithium ion coordination and transmission. In addition, by increasing the length of the π-conjugation and the number of distorted aromatic sites, the electrical conductivity and ionic conductivity can be improved. The electrical conductivity of the macromolecules of the disclosed subject matter can be at least one order of magnitude higher than that of the counterparts with shorter bands. In certain aspects, the electrical conductivity of the hPDI[n] family can increase with band extension. The improvement in electrical conductivity can be attributed to, for example, the length of the conjugated structure of hPDI[n]. Therefore, increasing the length of the conjugated band, for example, the twisted helical perylene diimide [6] (hPDI[6]) macromolecule can improve electrical conductivity.
[0019] In certain embodiments, the macromolecules of the disclosed subject matter can be formulated as cathodes. Such formulated cathodes can provide relatively high rate performance, which can reduce the charging time to less than about 1 minute, less than about 50 seconds, or less than about 40 seconds. In certain embodiments, a battery incorporating the macromolecules of the disclosed subject matter can be charged to about 67% in about 35 seconds or less. In addition, the output power density of the cathode can be as high as about 22,000 W / kg or as high as about 28,000 W / kg. In certain embodiments, the output power density can be at least about two orders of magnitude higher than a standard lithium-ion battery (LIB). The cathode of the disclosed subject matter incorporating the macromolecules disclosed herein can advantageously have high cycle stability, for example, after 10,000 charge-discharge cycles, the capacity decay is about 0.004% and about 0.002% per cycle for 7.7°C and 77°C, respectively. Therefore, the cathode of the disclosed subject matter can have high cycle stability without significant capacity decay. In addition, such a cathode can maintain its performance under high mass loading and high temperature conditions.
[0020] In certain aspects, when fabricated as cathodes in lithium-ion batteries, the macromolecules of the disclosed subject matter exhibit both high electrical conductivity and high ionic conductivity. In addition, such materials can exhibit power densities that are at least two orders of magnitude higher than certain conventional inorganic materials. In certain aspects, such materials can be charged to at least about 67% of their maximum capacity in less than about 1 minute or in 35 seconds. In addition, the materials of the disclosed subject matter can have high cycle stability and can operate for at least about 10,000 charge-discharge cycles without any significant capacity decay. Materials comprising the macromolecules of the disclosed subject matter can also be compatible with certain manufacturing techniques for commercial batteries without further modification, and can provide techniques for preparing sustainable, fast-charging, and long-lasting OBEMs, such as batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The patent or application file contains at least one drawing executed in color. Copies of this patent or patent application publication with color drawing(s) will be provided by the Office upon request and payment of the necessary fee.
[0022] Reference will now be made in detail to several exemplary embodiments of the disclosed subject matter illustrated in the accompanying drawings, in which like reference numerals refer to the same or functionally similar elements throughout the individual views, and which are used to further illustrate the various embodiments and to explain various principles and advantages of all disclosed subject matter.
[0023] Figure 1A provides a schematic structure of hPDI[6] in one embodiment of the disclosed subject matter. Figure 1B provides rate-capacity retention curves of hPDI[6] in one embodiment of the disclosed subject matter and other comparative organic cathode materials.
[0024] Figure 2A provides an iterative scheme for synthesizing hPDI[6] ribbons. Figure 2B provides an iterative scheme for synthesizing hPDI[6]-C 11 Figure 2C provides a solid-state thermogravimetric representation of hPDI[6] in one embodiment of the disclosed subject matter. 13 C NMR display.
[0025] Figures 3A to 3F show the electrochemical characterization of hPDI[n]. Figure 3A provides illustrative molecular structures of compounds with different lengths and modifications: hPDI[3] (blue), hPDI[4] (green), hPDI[5] (orange), hPDI[6] (red), PDI (black) and PDIv (cyan). Figure 3B provides the conductivity and band gap of hPDI[n]. Figures 3C and 3D provide the EIS and CV (scan rate: 1 mV / sec) of the cathode material, respectively. Figure 3E provides the cycling performance of hPDI[n] at 1A / g; Figure 3F provides the cycling performance of hPDI[6] at 7.7C and 77C in one embodiment of the disclosed subject matter.
[0026] Figure 4A Figure 4B provides a demonstration of the practical application of hPDI[6] in batteries. Figure 4A Provides an area mass loading of 5 mg / cm 2 FIG4B provides a demonstration of high mass loading of an hPDI[6] cell. FIG4B provides a demonstration of a 60°C high temperature test with a mass loading of 1 mg / cm2. FIG4C provides an image of an hPDI[6] cell powering an LED fan in one embodiment of the disclosed subject matter.
[0027] It is to be understood that both the foregoing general description and the following detailed description are exemplary, and are intended to provide further explanation of the disclosed subject matter. DETAILED DESCRIPTION
[0028] The disclosed subject matter provides molecular arrays of twisted macromolecular ladders, preparation thereof, and use in electrodes and lithium-ion batteries. Such molecular arrays can provide efficient performance when utilized in lithium-ion battery applications.
[0029] For the sake of clarity, but not limitation, the detailed description of the disclosed subject matter is divided into the following subsections:
[0030] I.Limited
[0031] II. Molecules
[0032] III. Synthesis
[0033] I.Limited
[0034] As used herein, the term "macromolecular ladder" refers to a class of macromolecules that are generally composed of repeating units linked together in a linear or branched structure. These molecules can be composed of a variety of materials including polymers, dendrimers, and other types of macromolecules. Regarding twisted macromolecular ladders, the repeating units can be composed of multiple aromatic rings connected by rigid connectors, forming a twisted 3D structure similar to a ladder. The resulting structure can be highly ordered with a unique topology, resulting in a variety of favorable properties, including high stability, high molecular weight, and rapid ion transport, promoting its application in lithium-ion batteries.
[0035] As used herein, the term "hPDI[n]" represents a spiroperylene diimide[6] macromolecule in which several redox-active PDI subunits may be fused together via ethylene subunits. In the case of hPDI[n], the number "n" refers to the number of hPDI units linked in the polymer chain. For example, hPDI[2] is a dimer consisting of two hPDI units linked together, while hPDI[3] is a trimer consisting of three hPDI units linked together, and so on. hPDI[n] compounds may have a variety of advantageous properties that make them useful for the synthesis of twisted macromolecular ladders. Thus, "PDIv" stands for "PDI-vinyl conjugated polymer."
[0036] As used herein, the term "OBEM" stands for organic battery electrode materials, a class of materials that may offer the opportunity to achieve relatively high power density without sacrificing energy density due to the material's molecular tunability that simultaneously provides high ion diffusion coefficients and high specific capacities.
[0037] As used herein, the term "Suzuki reaction" refers to a well-known organic chemical reaction that involves the coupling of two organic compounds, typically an aryl halide and an organic boronic acid, to form a new carbon-carbon bond. As embodied in the exemplary disclosed subject matter, the reaction can be used to extend the molecular chain of a spiroperylene diimide molecule from hPDI[n, n<6] to hPDI[6].
[0038] As used herein, the term "Mallory photocyclization" refers to a photochemical reaction involving the formation of a cyclic compound (e.g., a cyclic molecule) from an open-chain precursor molecule. As embodied in the exemplary disclosed subject matter, Mallory photocyclization is typically used to form the helical structure of a perylene diimide molecule. The reaction can be repeated several times to form a final product comprising a hPDI[n] molecule.
[0039] As used herein, the term "synthetic protocol" refers to a controlled, tuned and quantitative synthesis such as photocyclization, in which the reaction is designed to proceed to completion and the starting material is converted to the desired product. It is important to ensure that the final product is pure and of high quality.
[0040] As used herein, the term "pre-hPDI synthesis" refers to the production of a precursor form of PDI that has not yet undergone the post-translational modifications required to form the fully functional hPDI[n] isomer.
[0041] As used herein, the term "BMIDA-Bpin" stands for trans-2-(pinacol boronate) vinylboronic acid MIDA ester (the reactant during the Suzuki reaction with Br-hPDI).
[0042] As used herein, "HOMO" stands for the highest occupied molecular orbital, and "LUMO" stands for the lowest unoccupied molecular orbital, respectively. The energy difference between HOMO and LUMO is called the HOMO-LUMO gap, and its amplitude can be used to predict the strength and stability of molecular complexes. Generally, the larger the HOMO-LUMO gap of a compound, the more stable the compound.
[0043] As used herein, “ The "equation" refers to a mathematical equation used in electrochemistry to describe the effect of scan rate on the peak current of cyclic voltammetry electrochemical measurements. It can be used to calculate the peak current using the scan rate in the observed voltammogram.
[0044] As used herein, "area mass loading" refers to the mass of active material per unit area of an electrode. It can be used to assess the gravimetric energy density of an electrode. In an initial assessment, a higher mass loading may be preferred because it can better utilize area components such as carrier foil and separators.
[0045] II. Molecules
[0046] [Synopsis Structure]
[0047] In certain embodiments of the disclosed subject matter, twisted and fully conjugated macromolecules for fast-charging and long-life cathodes for lithium batteries are provided to address the relatively low intrinsic conductivity of certain OBEMs and improve their ability to achieve high rate performance and areal mass loading.
[0048] In certain embodiments, molecular designs of fully conjugated "ladder-type" macromolecules are provided. In certain aspects, effective members of this series are twisted helical perylene diimide [n] (hereinafter referred to as hPDI [n]) macromolecules, in which n redox-active PDI subunits can be fused together through ethylene subunits as shown in FIG. 1A . As in the structure in FIG. 1A , the twist dimensions, such as direction and angle, can be adjusted and coordinated according to the desired design.
[0049] In one embodiment of the disclosed subject matter, such twisted, ladder-conjugated, atomically precise macromolecules can be designed under four principles for organic electrodes to achieve excellent rate performance and cycling stability: (1) the redox-active PDI subunits can be characterized by high stability and fast redox kinetics; (2) the solubility of these macromolecules can be controlled, which can allow the design of materials that address the solubility issues from small molecules while exhibiting effective conjugation of the polymer structure; (3) the twisting of adjacent PDIs can facilitate lithium ion transport in solid materials and can improve ionic conductivity; (4) the defined fully conjugated ladder structure can provide high conductivity. In certain embodiments of the disclosed subject matter, the twisted helical perylene diimide macromolecule comprises hPDI [6].
[0050] For calculations of molecular structures, all quantum chemical calculations were performed using Jaguar (version 8.2, Schrodinger, Inc., New York, NY, 2013). 25 All geometries were optimized using the B3LYP functional and the 6-31G basis set. In the model compounds, the alkyl chain groups were replaced by hydrogen. The rocking conformation was calculated due to its stability in the solid state.
[0051] [Battery performance of hPDI[6] molecules]
[0052] As embodied herein, electrical performance with different OBEMs was measured via rate-capacity retention experiments. The results are shown in FIG. 1B , where the effective portion refers to the portion of the battery capacity that remains available after cycling the battery at a specific rate, and the number of cycles refers to the number of repetitions of the process. Notably, the effective portion is the percentage of the initial capacity of the battery that remains available after cycling the battery at a specific rate, and the unavailable remaining portion of the capacity represents the degradation of the battery over time. Controlled battery samples were tested with a variety of organic battery electrode materials (OBEMs) including PBQS, PPy, DAAQ-COF, DTT, and ADALS. These samples were charged for less than 5,000 cycles and showed a capacity retention curve that exhibited a sharp drop at rates below 20C. In contrast, the hPDI[6] battery sample was charged at a rate of 77C for up to 10,000 cycles and exhibited an effective portion of 80%. The rate-capacity retention curve of the hPDI[6] sample shows a gradual plateau with increasing rate, which indicates excellent battery performance and effective life in lithium-ion battery applications compared to other OBEMs tested.
[0053] III. synthesis
[0054] Compared to some synthetic methods for synthesizing hPDI[n] (up to n=4) that do not allow the synthesis of longer bands due to incomplete photocyclization, a reliable and efficient synthesis for hPDI[n] is provided herein. To address this problem, electrical conductivity and ionic conductivity can be designed and improved by increasing both the length of the π-conjugation and the number of distorted aromatic sites. A relatively long atomically defined ladder-type fully conjugated structure is formed.
[0055] As embodied herein, hPDI[n]-C 11 As a perylene diimide derivative, it is an intermediate product during the synthesis. It is a type of organic semiconductor material that can be used to develop organic electronic devices such as organic photovoltaic cells, organic light-emitting diodes, and organic field-effect transistors. For example, hPDI[2]-C 11 The molecule consists of 11 carbon atoms (C 11 ) is composed of two perylene diimide units connected by a flexible linker. The molecule has a planar rigid structure, which enables it to form a highly ordered film when deposited on a substrate. 11 Linkers can provide flexibility to the molecule, which can help improve its solubility and processability during synthesis.
[0056] In certain embodiments, an iterative synthesis scheme is performed involving two repetitions of the "Suzuki reaction-Mallory photocyclization" sequence that provides quantitative photocyclization, as shown in FIG2A (asterisks indicate the positions of the corresponding groups from the regioisomer). In this embodiment, hPDI[n]-C 11 Or iterative synthesis of hPDI[n]:
[0057] 1) Bromination of hPDI to DiBr-hPDI; 2) Suzuki reaction between DiBr-hPDI and BMIDA; 3) Synthesis of pre-hPDI[n+2]; 4) Synthesis of hPDI[n+2]-C 11 ; 5) synthesis of hPDI[n] during pyrolysis. As will be appreciated by those skilled in the art, this method can be flexibly varied, for example, via alternative process sequences of reactions. In addition, the skilled artisan will appreciate and understand that process parameters such as reagent volumes / concentrations, temperature and pressure are readily determined in order to achieve synthesis.
[0058] As embodied herein, according to the synthetic scheme, the shorter hPDI[2]-C 11 Preparation of hPDI[6]-C 11 hPDI[6]-C at 300°C to 400°C 11 Vacuum pyrolysis was performed to quantitatively remove the alkyl chains (see thermogravimetric analysis shown at the bottom of Figure 2A), which improved the gravimetric capacity by reducing the inactive mass and simultaneously made the material insoluble. 13 CNMR (nuclear magnetic resonance), infrared spectroscopy and MALDI (matrix-assisted laser desorption / ionization) mass spectrometry confirmed the structure of hPDI[6]. 13 C NMR confirmed the formation of hPDI[6].
[0059] In some embodiments, as shown in FIG. 3A , shorter hPDI[n] (n=3, 4, 5) ribbons are prepared under the same protocol and the conductivity of the hPDI[n] (n=3, 4, 5, 6) films is measured by a dual probe method. As shown in FIG. 3B , the conductivity of hPDI[5] and hPDI[6] can be an order of magnitude higher than that of the shorter ribbons. Thus, it is demonstrated that the conductivity of the hPDI[n] family increases significantly with ribbon extension. The HOMO-LUMO gap of the hPDI[n] ribbon is determined by its hPDI[n]-C 11The absorption maximum of the corresponding substance is estimated. The band gap of infinite hPDI[n] polymer is estimated to be 1.96 eV. Therefore, hPDI[6] (band gap of 2.00 eV) can be a good representative of the polymer hPDI[n] structure. Therefore, the improvement in conductivity can be derived from the long conjugated structure of hPDI[n]. These conductivities can come from undoped molecules, and the material can have a relatively high conductivity when reduced to its anionic form. In summary, increasing the length of the conjugated band can be an effective method to improve conductivity.
[0060] Example
[0061] Example 1: Synthesis of hPDI[6]
[0062] 1. Synthesis Overview
[0063] Materials. Unless otherwise stated, all chemicals were obtained from commercial sources and used as received. Flash chromatography (FC) was performed with silica 60 (230 mesh to 400 mesh; Fisher). Analytical thin-layer chromatography (TLC) was performed using 0.2 mm silica gel plates (Silica gel 60, F254, EMD Chemical).
[0064] MALDI-TOF. Mass spectrometry data were obtained at the Columbia University Mass Spectrometry Facility using a Bruker ultrafleXtreme MALDI TOF / TOF with a frequency tripled Nd:YAG laser (355 nm).
[0065] Solution NMR. Solution NMR was recorded on a Bruker 400MHz, 500MHz spectrometer. 1 H and 13 C NMR spectra. Chemical shifts for protons are reported in parts per million downfield from tetramethylsilane and referenced to residual protium in the NMR solvent (CHCl3: δ 7.26). Chemical shifts for carbon are reported in parts per million downfield from tetramethylsilane and referenced to the carbon resonances of the solvent (CDCl3: δ 77.0). Data are presented as follows: chemical shift, multiplicity (s = singlet, d = doublet, t = triplet, m = multit, b = broad, bm = broad multit), coupling constant in Hertz, and integral.
[0066] Solid State NMR (SSNMR). SSNMR experiments were performed on a 600 MHz magnet equipped with a Bruker NEO console using a 1.6 mm HFXY probe. All experiments were performed at ambient temperature with a magic angle spinning rate of 20 kHz. During signal acquisition, the 1 H- 13 The carbon spectrum was acquired with C cross polarization and decoupled at 100 kHz. The spectrum was acquired with a 90-echo pulse sequence. 1 H proton spectra to achieve a reasonable baseline. All carbon spectra were processed using an exponential window function with 200 Hz broadening. For the proton spectra, no apodization function was used. 13 The C chemical shift is referenced to the downfield carbon chemical shift of adamantane at 40.48 ppm, and 1 H chemical shifts were referenced to DSS solution.
[0067] Electronic Absorption (UV-Vis). Absorption spectra were obtained on a Shimadzu UV 1800 UV / vis spectrophotometer.
[0068] Powder X-Ray Diffraction (PXRD): PXRD was measured on a PANalytical XPert3 powder X-ray diffractometer on a rotating Si zero background plate.
[0069] 2. Synthesis steps
[0070] 2.1hPDI[n]-C 11 Iterative synthesis of
[0071] Bromination of hPDI is achieved as shown in the following chemical formula (1):
[0072]
[0073] Step 1: hPDI[n] was dissolved in 5mL of dichloromethane in a 20ml vial with a stirring bar. Excess bromine (400 equivalents) was added, followed by a small amount of iodine crystals. The solution was capped and stirred at room temperature. The reaction was monitored by TLC until only one spot was present. The bromine was then quenched with a saturated solution of sodium bisulfite and extracted with dichloromethane. The combined organic layers were dried over anhydrous magnesium sulfate and concentrated under reduced pressure. The solid was washed with MeOH, collected by filtration, and washed with cold MeOH to obtain the corresponding hPDI[n]-diBr.
[0074] DiBr-hPDI[3]: hPDI[3] (500 mg, 0.23 mmol) was converted to DiBr-hPDI[3] (530 mg, 99% yield) as a dark red solid according to step 1.
[0075] DiBr-hPDI[4]: hPDI[4] (400 mg, 0.14 mmol) was quantitatively converted to DiBr-hPDI[4] (422 mg, 99% yield) as a dark red solid according to step 1.
[0076] The Suzuki reaction of DiBr-hPDI is carried out as shown in the following chemical equation (2):
[0077]
[0078] Step 2: DiBr-hPDI[n], trans-2-(pinacol boronate) vinyl boronic acid MIDA ester (2.5 equivalents), anhydrous potassium phosphate (12 equivalents) and Pd(dppf)Cl2 (0.15 equivalents) were added to the Schlenk flask. The Schlenk flask was sealed with a rubber septum, and the headspace was evacuated and backfilled with nitrogen three times, and then THF (8mM) and water (20 equivalents) sprayed with nitrogen were added thereto. The reaction mixture was stirred at ambient temperature for 24 hours and concentrated in vacuo. The residue was redissolved in DCM, loaded onto a silica plug, and washed with dichloromethane / ethyl acetate (7:3) to remove unreacted starting material, mono-coupling product and other by-products. The product was then rinsed with tetrahydrofuran and concentrated in vacuo. The solid was washed with acetonitrile to remove unreacted trans-2-(pinacol boronate) vinyl boronic acid MIDA ester, collected by filtration, and washed with acetonitrile to obtain the product.
[0079] DiBmida-hPDI[3]: The product was obtained as a dark red solid according to step 2 (181 mg, 83%).
[0080] DiBmida-hPDI[4]: The product was obtained as a dark black solid according to step 2 (91 mg, 85%).
[0081] The synthesis of pre-hPDI[n+2] is achieved as shown in the following chemical formula (3):
[0082]
[0083] Step 3: DiMIDA-hPDI, iodine (2 equiv.) and THF (10 -3 The 1-hydroxy-2-nitropropene (2-hydroxy-2-nitropropene) of 1-nitropropene (2-hydroxy-2-nitropropene) is added into the Erlenmeyer flask. The flask is irradiated by four 150W white LED lamps for 24 hours. Remove the solvent in a vacuum, and the residue is redissolved in DCM, loaded on the silica plug, and washed with dichloromethane / ethyl acetate (7:3) to remove by-products. Then rinse the product with tetrahydrofuran (THF), and concentrate in a vacuum to make it stand the following without further purification.
[0084] Cyclization of DiBmida-hPDI[3]: The product was obtained as a dark solid according to step 3 (100 mg, 57%).
[0085] Cyclization of DiBmida-hPDI[4]: The product was obtained as a dark solid according to step 3 (46 mg, 51%).
[0086] The synthesis of pre-PDI[n][n=5,6] is achieved as shown in the following chemical formula (4):
[0087]
[0088] Step 4: Cyclized DiBmida-hPDI, 1-bromoperylene-3,4,9,10-tetracarboxylic acid diimide (PDI-Br, 2.2 equiv.), Pd(dppf)Cl2 (0.1 equiv.), and potassium carbonate (12 equiv.) were added to a vial. The headspace of the vial was evacuated under vacuum and backfilled three times with nitrogen. Air-free THF / H2O (v / v, 4:1, 2 mM) solution was then added to the reaction vessel via a syringe under a stream of nitrogen and sealed with a Teflon cap. The dark red solution was stirred at 57 °C for 12 hours and concentrated in vacuo. The residue was purified via column chromatography (DCM: hexane, 5:1) to give pre-hPDI.
[0089] Pre-hPDI[5]: The product was obtained as a dark red solid according to step 4 (110 mg, 74%).
[0090] Pre-hPDI[6]: The product was obtained as a dark black solid according to step 4 (34 mg, 55%).
[0091] hPDI[n+2]-C is realized as shown in the following chemical equation (5): 11 synthesis:
[0092]
[0093] Step 5: Dissolve pre-hPDI in chlorobenzene (0.1 mM) and add to a 100 mL threaded culture tube. Add iodine (4 equivalents) to the solution. The tube is sealed and placed in a pristine oil bath heated at 90°C, which is irradiated by four 150W white LED lamps for 4 hours. The reaction mixture is concentrated in vacuo, and the residue is purified via methanol washing to obtain hPDI.
[0094] hPDI[5]-C 11 : The product was obtained as a dark red solid according to step 5 (110 mg, 99% yield).
[0095] hPDI[6]-C 11: The product was obtained as a dark black solid according to step 5 (33 mg, 99% yield).
[0096] hPDI[2]-C was prepared by the described protocol. 11 hPDI[4]-C was synthesized with an overall yield of 40% 11 ,and 1 The H NMR spectrum matches the measured results well.
[0097] 2.2 The synthesis of hPDI[n] is achieved as shown in the following equation (6):
[0098]
[0099] Step 6: Place the hPDI[n]-C 11 A 4 ml vial of 100 μl of 1 ...
[0100] hPDI[3]: The product was obtained according to step 6 as a dark red solid (quantitative yield), which was detected and identified by NMR.
[0101] hPDI[4]: The product was obtained according to step 6 as a dark red solid (quantitative yield), which was detected and identified by NMR.
[0102] hPDI[5]: The product was obtained according to step 6 as a dark red solid (quantitative yield), which was detected and identified by NMR.
[0103] hPDI[6]: The product was obtained according to step 6 as a dark red solid (quantitative yield), which was detected and identified by NMR.
[0104] 2.3 Synthesis of PDIv
[0105] A mixture of 1,6-dibromoperylene-3,4,9,10-tetracarboxylic acid diimide and 1,7-dibromoperylene-3,4,9,10-tetracarboxylic acid diimide (200 mg, 0.23 mmol), trans-2-(pinacol borate) vinyl boronic acid MIDA ester (72 mg, 0.23 mmol), Pd(dppf)Cl2 (17 mg, 0.023 mmol) and potassium carbonate (385 mg, 2.8 mmol) were added to the vial. The headspace of the vial was evacuated under vacuum and backfilled with nitrogen three times. Air-free THF / H2O (v / v, 4:1, 2 mM) solution was then added to the reaction vessel via a syringe under a stream of nitrogen and sealed with a Teflon cap. The solution was stirred at 57°C for 12 hours and concentrated in vacuo. The mixture was ground with methanol and the solid was collected. The solid was subjected to a continuous Soxhlet extraction consisting of methanol, hexane and chloroform. The chloroform fractions were collected and dried to yield PDIv as a dark purple solid, which was detected and identified by NMR.
[0106] Example 2: Electrodes and electrochemical performance
[0107] [Electrode manufacturing.]
[0108] The active material was mixed with Super P carbon (C65, Imerys Graphite & Carbon) and poly (vinylidene fluoride) (PVDF) (Kynar Flex) in a ratio of 8: 1: 1 and ground in an agate mortar for half an hour. N-methyl-2-pyrrolidone (NMP) was then added to the mixture and the slurry was ultrasonicated for 2 hours. After all materials were thoroughly mixed, the slurry was drop cast onto a carbon paper current collector (Fuel Cell Store). The coated electrodes were dried at 60 ° C for 2 hours and then dried in a vacuum oven at 110 ° C overnight. For performance testing and pouch cell manufacturing, the average active material loading was about 1 mg / cm, and for high area mass loading tests, the average active material loading was 5 mg / cm.
[0109] [Coin cell battery assembly.]
[0110] CR 2032 coin cells were assembled in an argon-filled glove box with both water and oxygen levels <0.1 ppm using a lithium metal disk as the anode, a thin polyethylene separator (10 μm), approximately 100 μL of an electrolyte of 1 M LiPF6 in ethylene carbonate (EC) / diethyl carbonate (DEC) (1:1 by volume) (LP40), and the fabricated cathode.
[0111] [Pouch cell battery assembly.]
[0112] In an argon-filled glove box with both water and oxygen levels <0.1 ppm, a square cathode (4 cm × 5 cm) and a lithium metal foil anode (4 cm × 5 cm) were separated by a thin polyethylene separator and wetted with 750 μl of LP40 electrolyte. The stack was placed in a plastic bag (about 6 cm × 7 cm) in contact with an aluminum sheet for the cathode and a nickel sheet for the anode as a current collector (thickness of about 0.13 mm) and sealed under vacuum using a vacuum heat sealer. The battery was clamped in a vise with flat blocks on both sides at a pressure of about 100 pounds per square inch to ensure good contact between all components.
[0113] [Electrochemical measurements.]
[0114] All CV tests and EIS were performed with a VMP3 multi-channel potentiostat from Bio-Logic. For the EIS test, the assembled coin cell was left to rest for 12 hours and then cycled three times and stopped at a voltage of 2.3V close to its redox potential, and then the cell was prepared for electrochemical testing. Cyclic testing was performed using a Landt battery tester. Electrochemical impedance spectroscopy (EIS): The amplitude of the EIS was 10 mV, and the frequency range was 0.1 Hz to 1 MHz. About 6 frequencies were taken in each decade, and the total measurement time was about 1 minute.
[0115] [Diffusion coefficient analysis.]
[0116] 1mV second -1 To 25mV seconds -1 Cyclic voltammetry was performed on the assembled coin cell at a scan rate of . The peak current (i p ) is plotted against the square root of the scan rate (υ).
[0117] To evaluate the electrochemical performance of hPDI[n], an hPDI[n] electrode was prepared by drop casting a slurry of 80 wt% hPDI[n], 10 wt% carbon black (as a conductive agent), and 10 wt% polyvinylidene fluoride (PVDF; as a binder) in N-methyl-2-pyrrolidone onto carbon paper. Such a high ratio of active material can be easily used for testing of inorganic materials, but may be higher than those easily tested in organic materials. The electrode was assembled in a 2032 coin cell with lithium metal and an electrolyte of 1M LiPF6 in diethyl carbonate (DEC) / ethylene carbonate (EC) (1:1 by volume). For comparison, PDI-vinyl conjugated polymer (PDIv) and PDI monomer with similar theoretical weight capacity were tested. As shown in Figure 3C, the electrochemical impedance spectroscopy (EIS) of these cells showed that the charge transfer resistance (Rct) of hPDI[n] can decrease as the band length becomes longer, PDI exhibits a relatively high Rct of 1500Ω, and PDIv can exhibit an Rct similar to that of hPDI[3]. Rct is correlated with the conductivity of the original material. The relatively low charge transfer resistance (47Ω) of hPDI[6] can contribute to the fast electron transport, which can come from fast intramolecular charge transfer and intermolecular charge transfer.
[0118] Cyclic voltammograms (CV) were performed to examine the electrochemical behaviors of (h)PDI[n] (n=1, 3, 4, 5, 6) and PDIv (Figure 3D). As shown in Figure 3D, at a scan rate of 1 mV / s, hPDI[n] exhibited a broad and reversible redox pair at a potential of 2.2 V relative to Li / Li+, matching the redox events of the PDI subunit. The peak current of hPDI[n] increased with increasing band length, indicating improved electrochemical performance with increasing [n]. Analysis of the double logarithmic plots of scan rate (v) versus peak current (i) showed that the hPDI[n] band exhibited surface-controlled kinetics, PDI exhibited diffusion-controlled behavior, and PDIv was in between. Therefore, molecular distortion sites in hPDI[n] can facilitate lithium ion transport. Using the The lithium ion diffusion rate of the equation shows the effect of distortion on lithium ion transport. The measurement results are shown in Table 1 below.
[0119] Table 1
[0120]
[0121] Specific capacity. Theoretical capacity.
[0122] "Obtained from CV." Obtained from EIS.
[0123] For the hPDI[n] series, as the length of the macromolecule increases from hPDI[3] (1.8×10 -11 cm 2 / second) to hPDI[6](5.7×10 -10 cm 2 / second), D Li + (Li + Diffusion coefficient of ions, cm 2 / sec) increased. However, the PDIv conjugated polymer showed a 1.9×10 -11 cm 2 / sec. Therefore, the lower ionic conductivity in shorter oligomers and PDIv polymers may be due to the lack / absence of well-defined positions of carbonyl groups resulting from molecular distortion in longer oligomers. This was confirmed by EIS and galvanostatic intermittent titration technique (GITT). The high ionic conductivity of hPDI[6] may be due to the twisted imide in the long oligomer acting as a conveyor belt for lithium ions.
[0124] With improved electrical conductivity and ionic conductivity, hPDI[6] as a cathode material can achieve superior power density and first-class cycling stability. Figure 3E shows the increased rate performance of PDI, PDIv, hPDI[3] and hPDI[6] at different discharge rates from 0.1A / g to 10A / g. At 0.1A / g (0.77C), hPDI[6] reaches 99% of the theoretical specific capacity value. hPDI[6] shows almost no loss in capacity until the current rate is increased to 2A / g. Even at a 100-fold current rate of 10A / g (77C), hPDI[6] has a specific capacity of 87mAh / g. Therefore, the hPDI[6] battery can be charged to 67% of its capacity in 35 seconds, corresponding to a specific power density of 22,000W / kg. This high rate performance of hPDI[6] can be attributed to both the high ionic conductivity from the molecular twisting and the electrical conductivity from the precisely defined "ladder-type" conjugated structure. As shown in Figure 3F, the hPDI[6] cathode can exhibit high cycling stability. At 1A / g, hPDI[6] has an initial capacity of 126mAh / g and retains 86mAh / g after 10,000 cycles at 7.7C, corresponding to a capacity decay of only 0.004% per cycle. At higher rates (10A / g, 77C), the hPDI[6] cathode also maintains its stability, with a capacity retention of 84% after 10,000 cycles, corresponding to an ultra-low capacity loss of 0.0017% per cycle. Overall, hPDI[6] can be a fast-charging cathode, which may be due to its high power density and cycling stability.
[0125] In addition to high rate capability and cycle life, hPDI[6] cathodes can also maintain their high performance under both high mass loading and high temperature conditions. To date, most lithium-ion batteries using organic materials as electrodes have been limited to about 0.1 mg / cm due to the inherent low conductivity of the materials. 2 Up to 1mg / cm 2 In this embodiment, a low mass loading of active material was produced. 2 electrodes to test the high mass loading capacity of hPDI[6]. Figure 4A As shown in Figure 4B, the cell with high mass loading of hPDI[6] retains 96% of the theoretical specific capacity (121 mAh / g) at 1 A / g, with high cycling stability of 75% capacity retention after 3,000 cycles. In addition, as shown in Figure 4B, the hPDI[6] cathode also exhibits reliable high temperature performance, with an initial capacity of 131 mAh / g and a capacity retention of 71% after 1,000 cycles at 60°C.
[0126] Example 3: Practical application of hPDI[6] battery
[0127] As embodied herein, pouch cells were fabricated to power a commercial LED fan, for example, to provide practical relevance of the hPDI[6] material. The fan operated at a voltage and current of 4 V to 5 V and 200 mA to 300 mA, respectively, corresponding to a total power of about 1.12 W. A pouch cell (4 cm × 5 cm) was constructed with a cathode composite material containing 20 mg of hPDI[6]. Two pouch cells were used to provide sufficient voltage. As shown in FIG4C , the battery powered the LED fan for 40 seconds, corresponding to a power density of 28,000 W / kg. Such a power density is 50 times higher than that of current state-of-the-art LIBs.
[0128] At least from the examples, a twisted atomically defined hPDI[6] macromolecular ladder is provided, which has high ionic conductivity and electrical conductivity as a fast charging and long-life battery cathode. hPDI[n] is efficiently synthesized via a newly developed iterative scheme. The electrical conductivity of hPDI[n] can be designed and improved by increasing the conjugation of the band. In addition, longer hPDI[n] bands introduce more twisting sites and accelerate ion transport. With improved conductivity and ion diffusion rate, the hPDI[6] cathode has a power density two orders of magnitude higher than conventional inorganic materials. A battery with hPDI[6] as a cathode can be charged to 67% of its maximum capacity in 35 seconds. The stable structure of hPDI[6] allows it to be cycled 10,000 times without any significant capacity decay. In addition, hPDI[6] is also compatible with existing manufacturing due to its high mass loading and low conductive additive ratio, meaning that it can be used in batteries without further modification. Therefore, both conjugation and twisting can improve the rate performance of organic materials. Thus, a streamlined chemical model for achieving fast-charging, long-life, and sustainable battery electrodes can be provided.
Claims
1. A molecular array of twisted and conjugated macromolecular ladders, comprising: One or more macromolecular ladders twisted and conjugated at one or more aromatic sites. 2 . The molecular array according to claim 1 , wherein the macromolecule is configured to have at least a ladder-type conjugated structure and comprises a plurality of hPDI[n] oligomers, wherein n is an integer from 1 to 6. 3 .
3. The molecular array of claim 1, wherein the macromolecular ladder comprises hPDI[6] oligomers.
4. A method for synthesizing molecular arrays of twisted and conjugated macromolecular ladders, comprising: (a) preparing a precursor comprising a plurality of hPDI[n], wherein n is an integer from 1 to 6; (b) polymerizing the precursor by repeated Suzuki-Mallory polymerization process to form a twisted and conjugated macromolecular ladder having a ladder-type conjugated structure and comprising the hPDI[n].
5. The method of claim 4, wherein the hPDI[n] oligomer is hPDI[6].
6. The method of claim 4, wherein the PDI subunit is selectively fused via an ethylene subunit.
7. The method of claim 4, wherein the polymerization process includes modeling the conjugation length and twist of the macromolecular ladder.
8. The method of claim 4, wherein the hPDI[n] is composed of hPDI[n]-C 11 preparation.
9. The method of claim 4, wherein the hPDI[n] has a conjugated and twisted band structure.
10. An electrode for a lithium ion battery, comprising the molecular array according to claim 1.
11. The electrode of claim 10, wherein the molecule is formulated as a cathode.
12. A lithium ion battery comprising the lithium ion electrode according to claim 11.